Landscapes and Landforms of Portugal - Vieira, Gonçalo (2020)
Landscapes and Landforms of Portugal volume presents, for the first time, a series of synthesis chapters on landscape highlights of mainland Portugal, covering a wide diversity of geomorphological settings. These are presented with language and graphic styles that try to bridge-the-gap from professional scientists to undergraduate students, while being also accessible to all those interested in the earth sciences, to help for a better understanding of landscape evolution and specific features of the Portuguese landforms. The authors are physical geographers and geologists, mostly from Portuguese research institutions, all of them having had conducted research in the regions which they present. The main objective of the book is to provide a good overview of the geomorphology of Portugal, but also of its links with human occupation of the territory, geohazards and geoheritage management. This book is a tribute to Prof. António de Brum Ferreira, who has been an inspiration for generations of geomorphologists and students. Landforms and Landscapes of Portugal volume is organized in five thematic parts, i.e. 1. geomorphological setting, dynamics and hazards, 2. coasts, 3. mountains and valleys, 4. urban areas, 5. geoconservation and geoparks. In each part, chapters are ordered geographically from north to south, covering most of mainland Portugal (Fig. 1) [...]